Simultaneous tracheal and esophageal reconstruction for thyroid cancer involving trachea and esophagus using a free bipaddled posterior tibial artery perforator flap. Issue 9 (25th June 2019) - Liu, Jun; Ren, Jianjun; Lv, Dan; Wang, Ji; Deng, Di; Li, Linke; Wang, Haiyang; Chen, Fei
Abstract: Background: Simultaneous tracheal and esophageal reconstruction after tumor resection is a great challenge. Here we present an innovative operative technique to simultaneously reconstruct tracheal and esophageal defects, in which a free posterior tibial artery perforator flap was made into a free bipaddled flap to cover both tracheal and esophageal defects. Methods: A free bipaddled posterior tibial artery perforator flap was utilized to conduct simultaneous tracheal and esophageal reconstruction for a 72‐year‐old female patient with papillary thyroid carcinoma and massive trachea and esophagus invasion, who underwent radical resection. Results: Satisfactory breathing and swallowing functions were gained independent of nasal feeding and tracheotomy. Voice was still hoarse due to tumor invasion of left recurrent laryngeal nerve. During a period of 2‐year follow‐up, no sign of tumor recurrence was observed. Conclusion: A free bipaddled posterior tibial artery perforator flap could be a decent choice for simultaneous reconstruction of large tracheal and esophageal defects.